Perceptions Of Accounting Lecturers And Students On The Ethics Of Reporting (Case Study At Dili Timor- Leste High School) - Estanislau Bana; Sutrisno T; Zaki Baridwan (LPPM Institut Teknologi dan Sains Mandala, 2022)
This research was conducted at the Dili Tmor-Leste College, this study aims to determine the differences in the perceptions of Lecturers and Accounting students on the ethics of preparing financial statements as seen from Misstatements in financial statements, Disclosure of sensitive information, Cost benefits of disclosure of information and accountability for the use of financial statements. The population in this study was 268. Questionnaires were randomly distributed to both Lecturers and Students of the Accounting Department in Semester V and VII of Dili Timor Leste, with details of 112 for Accounting Students in semester V, VII and 48 for Lecturers of Dili Timor Leste. The data analysis technique used was qualitative data in this study, researchers carried out processing techniques and quantitative data analysis. The formula used is the t-test formula or t-test and paired sample t-test. Based on the results of the research analyzed, it can be concluded that: (1)The results of the calculation of the analysis of the T-test difference with the Independent Sample T-test obtained a probability value of 0.0544 > 0.05, then H1 is rejected, meaning there is no significant difference in the perceptions of lecturers and students on the ethics of preparing financial statements as seen from the Sala serving in financial reports between Accounting Students and University Lecturers in Dili Timor Leste. (2) The results of the calculation of the analysis of the T-test difference with the Independent Sample T-test obtained a probability value of 0.020 <0.05, then H2 is accepted, meaning that there is a significant difference in the perception of students and Dili Timor Leste College Lecturers on the ethics of preparing financial statements as seen from the disclosure sensitive information between Accounting Students and University Lecturers in Dili Timor Leste. (3) The results of the calculation of the analysis of the T-test difference with the Independent Sample T-test obtained a probability value of 0.0105 <0.05 then H3 is accepted meaning that there is a significant difference in student perceptions of the ethics of preparing financial statements as seen from the cost benefits of information disclosure between students Accounting and Lecturer at Dili Timor Leste.The results of the calculation of the analysis of the T-test difference with the Independent Sample T-test obtained a probability value of 0.0480 <0.05, then H4 is accepted, meaning that there is a significant difference in student perceptions of the ethics of preparing financial statements as seen from the accountability for the use of financial statements between students. Accounting and Lecturer at Dili Timor Leste.